Analisis Pengaruh Brand Image, Harga Dan Iklan Terhadap Keputusan Pembelian Smartphone Samsung : (Studi Pada Mahasiswa STBM Dua Sudara Bitung ) - Oktaviani Ramenusa; Agnes R. Maxam (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
Analysis of the Effect of Brand Image, Price and Advertising on Samsung Smartphone Purchase Decisions (Study on STBM Dua Sudara Bitung Students) is a study conducted with the aim of knowing the effect of Brand Image, Price, and Advertising on Purchase Decisions both independently and together. This study uses the analytical method used in the study, namely multiple regression analysis using SPSS. This study used 82 samples of respondents and data collection techniques in the form of distributing questionnaires. The results obtained show that Brand Image, Price, Advertising, together affect the Samsung Smartphone Purchase Decision with an error rate of 5%, because the results of the hypothesis explain that the calculated F value is greater than Ftable at a significant level of 0.00, therefore it can be concluded that Brand Image, Price, Advertising together influence the Samsung Smartphone Purchase Decision. Partially shows that the Brand Image, Price, Advertising variables have a partial effect on the Samsung Smartphone Purchase Decision.